Barriers and Support for Family Caregivers in Caring for Older Adults with Dementia: A Qualitative Study in Indonesia - Rita Hadi Widyastuti; Junaiti Sahar; Etty Rekawati; Aria Kekalih (Nurse Media Journal of Nursing, 2023)
Background:  Understanding the barriers and support that family caregivers face when caring for older adults with dementia is critical for improving the quality of  dementia care. However, research in this area remains limited in Indonesia. Purpose: This study aimed to explore the barriers and support for family caregivers in caring for older adults with dementia in Indonesia.Methods: A descriptive phenomenological study was conducted among 15 family caregivers who cared for older adults with dementia. Purposive sampling was used to recruit the participants. Inclusion criteria included primary family caregivers who provided care for four hours per day for at least six months, were proficient in Indonesian, assisted older adults in daily activities, and were capable of expressing their experiences. Data were collected using in-depth semi-structured interviews and analyzed using the Colaizzi method.  Results: This study found that family caregivers faced barriers during the care of older adults with dementia, which have decreased the quality of care. These barriers included inadequate knowledge and skills of family caregivers regarding dementia, stigma, lack of knowledge and awareness in the community, limited availability of healthcare services, and healthcare professionals’ lack of knowledge about dementia. On the other hand, support received by family caregivers within the family, support from other family caregivers, and education provided by NGOs about caring for someone with dementia have shown a positive impact in reducing the burden on caregivers and improving the quality of care. Therefore, appropriate support is essential for family caregivers caring for older adults with dementia.Conclusion: This study showed that barriers originating from family caregivers, community awareness, access to health services, and barriers from health workers have impacted poor quality of care, while the support of families, fellow family caregivers, and NGOs have contributed to good quality of care. Further studies are needed to explore the perspectives of family caregivers representing different cultures in Indonesia.